Nursing of a patient with infertility induced by fallopian tube obstruction treated with midnight-midday ebb flow Traditional Chinese Medicine enema (子午流注择时中药灌肠治疗输卵管阻塞性不孕症1例的护理) - ZHANG Xihong (张昔红); LU Ying (卢英); WANG Xujing (王雪静); YANG Man (杨曼) (中西医结合护理)
This paper summarized the treatment effect of midnight-midday ebb flow Traditional Chinese Medicine enema in treating one case of infertility induced by fallopian tube obstruction. According to the effect evaluation and follow-up results, the midnight-midday ebb flow Traditional Chinese Medicine enema was a safe and effective treatment for infertility induced by fallopian tube obstruction. (运用子午流注理论指导的中药灌肠技术, 对1例输卵管阻塞引起的不孕症患者进行治疗, 分析治疗前后的疗效及治疗后随访的妊娠情况, 结果显示子午流注理论指导下的中药灌肠技术治疗输卵管阻塞性不孕症安全有效。)